Gyrators, simulated inductors and related immittances realizations and applications - Senani, Raj; Bhaskar, Data Ram; Singh, Vinod Kumar, 1977-; Singh, Abdhesh Kumar (Materials, circuits and devices series, 2020)
This book provides coverage of the major gyrator circuits, simulated inductors and related synthetic impedances. It offers a review of research in this field to date, and includes a wide range and number of circuit examples, along with their relevant design equations, limitations, performance features, advantages and shortcomings